2021
DOI: 10.3390/ijerph182111286
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Sedentary Time and Behaviour in Children and Adults: A Systematic Review and Meta-Analysis

Abstract: The aim of this meta-analysis was to quantify the change in sedentary time during the COVID-19 pandemic and its effect on health outcomes in the general population. One thousand six hundred and one articles published after 2019 were retrieved from five databases, of which 64 and 40 were included in the systematic review and meta-analysis, respectively. Studies were grouped according to population: children (<18 years), adults (18–64 years) and older adults (>65 years). Average sedentary time was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
119
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 109 publications
7
119
0
6
Order By: Relevance
“…To our knowledge, this is the first Italian study to provide objective and self-reported PA data aiming at assessing the long-term effects of COVID-19 on children’s PA behaviours as recommended by Yomoda et al [ 12 ] Moreover, in line with our findings, a recent systematic review with metanalysis performed by Runacres et al found a strong impact of the COVID-19 pandemic on children’ sedentary time. However, all the included studies used only self-reported measurements to assess sedentary time and,furthermore, they were not focused on a longer impact of COVID-19 but on the effects of lockdown or similar restrictions (such as school closures or homestay requirements) [ 37 ]. Considering that PA habits in childhood are of great importance as children who are active in their youth are more likely to continue of being active into adulthood [ 38 ] and that the effects of COVID-19 could be prolonged, public health stakeholders should consider these findings to prevent the negative effects of PI among children by promoting strategies to restore PA to a sufficient level.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first Italian study to provide objective and self-reported PA data aiming at assessing the long-term effects of COVID-19 on children’s PA behaviours as recommended by Yomoda et al [ 12 ] Moreover, in line with our findings, a recent systematic review with metanalysis performed by Runacres et al found a strong impact of the COVID-19 pandemic on children’ sedentary time. However, all the included studies used only self-reported measurements to assess sedentary time and,furthermore, they were not focused on a longer impact of COVID-19 but on the effects of lockdown or similar restrictions (such as school closures or homestay requirements) [ 37 ]. Considering that PA habits in childhood are of great importance as children who are active in their youth are more likely to continue of being active into adulthood [ 38 ] and that the effects of COVID-19 could be prolonged, public health stakeholders should consider these findings to prevent the negative effects of PI among children by promoting strategies to restore PA to a sufficient level.…”
Section: Discussionmentioning
confidence: 99%
“…People in the United States who worked from home reported more time sitting than those who continued to work on-site based on self-report measurements and recall [ 19 ]. A systematic review and meta-analysis including 64 studies, using both subjective and objective measurements, conducted during year 2020 in European (Sweden not included), North and South American, Asian, and African countries revealed an increase in sedentary time during the pandemic irrespective of sex, age, and lockdown [ 20 ]. A Canadian study including self-report measurements of current PA found that people who were already physically inactive had the greatest decrease in their PA levels.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, studies worldwide demonstrate decreases in PA and increases in sedentary behavior during the COVID-19 pandemic across various populations [ 18 , 20 , 29 ]. Notably, studies also indicate no change or even increased PA among population groups [ 30 ], which points to the need to further improve our understanding regarding variations in change in PA and sedentary behavior during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review concluded that most studies reported decreases in PA and increases in sedentary time/behaviours during the COVID-19 restrictions in both adults and children [7]. Furthermore, Runacres et al [39] systematic review and meta-analysis demonstrated that children's sedentary time increased the most (159.5 ± 142.6 min•day −1 ), compared to 126.9 ± 42.2 min•day −1 and 146.9 ± 22.0 min•day −1 in adults and older adults, respectively. Overall, children's and adolescent's PA was influenced by factors at each of the five levels: individual (mainly psychological), social (family and structured support), environmental (area of residence and resources), and policy.…”
Section: Discussionmentioning
confidence: 99%